Baked beans on toast and beating the gender odds - Devlin, Marcia (Journal of University Teaching and Learning Practice, 2022)
This invited Commentary examines responses to the book, Beating the Odds: A practical guide to navigating sexism in Australian universities. The book is relevant to the theme of the Special Issue, as women leading teaching and learning are doing so in a sexist environment that limits their opportunities to lead and that under-values their contributions when they do manage to achieve leadership roles. The editors invited me to write this Commentary, explaining that they were seeking “… a contemporary, thought-provoking piece by a leader in the topic of the Special Issue”. They suggested the Commentary might be “…an examination of the impact of the book and the emotive response it has generated in higher education”. Reactions to the book are discussed in terms of: resonance with the book’s contents; value for young/early career women; value for men; mixed emotions and value in taking action. The Commentary ends with a call to action related to baked beans on toast.